2012
DOI: 10.1590/s0102-33062012000300010
|View full text |Cite
|
Sign up to set email alerts
|

Estudo fitoquímico de folhas de Solanum lycocarpum A. St.-Hil (Solanaceae) e sua aplicação na alelopatia

Abstract: RESUMO(Estudo fitoquímico de folhas de Solanum lycocarpum A.St.-Hil (Solanaceae) e sua aplicação na alelopatia). Solanum lycocarpum A.St.-Hil (Solanaceae) é um arbusto típico da região central do Brasil (Cerrado). A atividade alelopática do extrato aquoso de folhas e frutos dessa espécie já foi verificada em estudos anteriores. O objetivo desse trabalho foi avaliar a atividade alelopática de diferentes extratos de S. lycocarpum na germinação e crescimento de quatro espécies-alvo. As folhas foram coletadas, sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
(42 reference statements)
0
14
0
6
Order By: Relevance
“…Although germination is considered less sensitive to the presence of allelochemicals (Oliveira et al, 2012), the interference of tough lovegrass extracts on this parameter was found in this work, which proves the autotoxic effect of these extracts, because germination was affected 5 even in the lowest concentration used. In general, the preparation of aqueous extracts and subsequent tests of its effects on the germination and growth of target species has been acknowledged as a classic process in the field of allelopathy (Inderjit and Dakshini, 1995).…”
Section: Initial Growth Bioassaymentioning
confidence: 47%
See 2 more Smart Citations
“…Although germination is considered less sensitive to the presence of allelochemicals (Oliveira et al, 2012), the interference of tough lovegrass extracts on this parameter was found in this work, which proves the autotoxic effect of these extracts, because germination was affected 5 even in the lowest concentration used. In general, the preparation of aqueous extracts and subsequent tests of its effects on the germination and growth of target species has been acknowledged as a classic process in the field of allelopathy (Inderjit and Dakshini, 1995).…”
Section: Initial Growth Bioassaymentioning
confidence: 47%
“…After this period, the material was filtered and its pH was determined. Extracts within the normal pH values were used for further experiments (between 4.0 and 7.0) ( Table 1) (Oliveira et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the allelopathic effect of the 100VEG extract was three times higher than the one observed in the 200REP extract. Considering that the pH of the extracts was in the appropriate range for the type of test (Oliveira et al, 2012) and that the values were similar among the extracts, the variation in the germinability and in the GSI is attributed to the combined effect of the N and of the phenology. The relation between the allelopathic activity and the maturity of plants was observed in sorghum (Sorghum sp., Poaceae) (Marchi et al, 2008) and in fenugreek (Trigonella foenum-graecum, Fabaceae) (Omezzine et al, 2014), in which plants harvested at the vegetative stage originated more allelopathic extracts compared to those elaborated with plants in a more advanced stage of development, thus it can be deduced that this fact occurred due to the increase in the amount of bioactive compounds.…”
Section: Resultsmentioning
confidence: 99%
“…No estudo realizado por Oliveira et al, (2013) o extrato acetato etílico de folhas de Solanum cernuum (Solanaceae) promoveu efeitos fitotóxicos sobre a germinação e vigor de plântulas de sorgo, alface e picão-preto. Utilizando extratos de Solanum lycocarpum (Solanaceae) de polaridades variadas, Oliveira et al, (2012) observaram que os efeitos inibitórios mais acentuados sobre o crescimento inicial das plântulas de cebola, alface, tomate e agrião foram promovidos pelo extrato acetato etílico.…”
Section: Discussionunclassified